MEMBANGUN IKLIM ORGANISASI MADRASAH MELALUI PERAN KEPALA MADRASAH DALAM UPAYA MENINGKATKAN MOTIVASI KERJA DI MIN 1 PONOROGO - Nazula, Desy (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
Motivation is a crucial element that drives enthusiasm for a teacher's work. However, a decrease in motivation can result in a lack of enthusiasm for learning innovation, with the impact mainly felt by students through monotonous and less varied learning. As a leader, the principal is expected to play a vital role in building and maintaining teacher motivation. This research uses a descriptive qualitative approach focusing on the organizational climate and the role of the madrasa head in increasing teacher work motivation at MIN 1 Ponorogo. This research aims to determine the madrasa head’s role in increasing teacher motivation. The research results show that an excellent organizational climate, mainly through democratic leadership, positively impacts teacher performance. The madrasa head at MIN 1 Ponorogo is influential in providing motivation, involving teachers in decision-making, and creating a collaborative work environment.